Weighing paper‐assisted magnetic ionic liquid headspace single‐drop microextraction using microwave distillation followed by gas chromatography–mass spectrometry for the determination of essential oil components in lavender. Issue 2 (27th November 2020) - Chen, Ping; Liu, Xin; Wang, Lili; Wang, Caijuan; Fu, Jihong
Abstract: Weighing paper‐assisted magnetic ionic liquid headspace single‐drop microextraction using microwave distillation followed by gas chromatography–mass spectrometry was successfully developed to determine the essential oil components in lavender. The magnetic ionic liquid 1‐octyl‐3‐methylimidazolium tetrachloroferrate was successfully synthesized and used as the optimal extraction solvent. An aliquot of 9 μL of magnetic ionic liquid could be stably suspended on the weighing paper for long time extraction. The increase of the extractant volume resulted in a significantly enhanced in extracting efficiency of the weighing paper‐assisted magnetic ionic liquid headspace single‐drop microextraction than traditional headspace single‐drop microextraction method. In this experiment, the optimal conditions were 1‐octyl‐3‐methylimidazolium tetrachloroferrate as the extraction solvent, extraction time of 12 min, microwave power of 600 W, cyclohexane as back‐extractant and sample amount of 30 mg. The developed method was successfully applied to analyze 16 lavender samples from three different harvest years. A total of 39 compounds in lavender were identified and the principal component analysis provided a clear separation between those lavender samples harvested in different years. The results indicated that the proposed weighing paper‐assisted magnetic ionic liquid headspace single‐drop microextraction is a novel, fast, simple and sensitive microextration technique for the determination of the essential oil components in lavender.